Peningkatan Hasil Belajar Peserta Didik dalam Pembelajaran Tematik Terpadu Menggunakan Model Discovery Learning Kelas IV SD - Kurnia, Rahmi; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This Research aims to describe the improvement of integrated thematic learning outcomes by using Discovery Learning model in class IV SD Negeri 04 District paninggahan solok. Unitages Research Research class with qualitative and quantitative approaches. The study carried out two cycles. Research Data in the form of observation and test results. The body In this study is teacher and grade IV students. Research results of RPP cycle I 76, 56% (C), Cycle II 93, 75% (SB). The implementation of learning aspects of my teacher's cycle is 81, 26% (B), Cycle II 90, 6% (SB). Aspects of student Cycles I 81, 26% (B), Cycle II 90, 6% (SB). Student Learning Results Cycle I 66, 53, Cycle II to 87. It can be concluded in research that the Discovery Learning model can improve the results of integrated thematic Learning.